ЗАСОЛЕННОСТЬ ПОЧВ ЮЖНОГО ПРИАРАЛЬЯ - Жумамуратов, А.; Сдиков, И.М.; Жумамуратов, М.А.; Аджимуратова, Д.М. (SCIENCE and SOCIETY, 2025)
This article presents the state of soil salinity in the Republic of Karakalpakstan, located on the southern shore of the Aral Sea. The soils of the Muynak district, located near the Aral Sea, contain 4.7%, the soils of the Nukus district, located in the center, contain 2.7%, and the soils of the Ellikkala district, the most remote district, contain 1.8% of the sodium element. During the analysis of the chemical composition of atmospheric dust and soils of the Muynak district, their CC was calculated.